2020
DOI: 10.1186/s12989-020-00381-z
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ti level in the human placenta and meconium and evidence of a materno-foetal transfer of food-grade TiO2 nanoparticles in an ex vivo placental perfusion model

Abstract: Background Titanium dioxide (TiO2) is broadly used in common consumer goods, including as a food additive (E171 in Europe) for colouring and opacifying properties. The E171 additive contains TiO2 nanoparticles (NPs), part of them being absorbed in the intestine and accumulated in several systemic organs. Exposure to TiO2-NPs in rodents during pregnancy resulted in alteration of placental functions and a materno-foetal transfer of NPs, both with toxic effects on the foetus. However, no human dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 68 publications
5
62
0
Order By: Relevance
“…( 2015 ) E 171, anatase, d50 = 260 nm1Qualitative analysis in blood, methodology highly reliable Guillard et al. ( 2020 ) E 171, anatase, 20–440 nm (mean 104.9 nm (SEM‐EDX), 55% nanoparticles1Quantitative analysis in tissues, methodology reliable with some limitations Disdier et al. ( 2015 ) TiO 2 NPs, P25 (15–24 nm)1Quantitative analysis in blood and tissues, methodology reliable with some limitations Kreyling et al.…”
Section: Appendix G – Description Of Test Materials Scoring For Nanoscale Consideration and Internal Exposure For Toxicokinetic Studiesmentioning
confidence: 99%
“…( 2015 ) E 171, anatase, d50 = 260 nm1Qualitative analysis in blood, methodology highly reliable Guillard et al. ( 2020 ) E 171, anatase, 20–440 nm (mean 104.9 nm (SEM‐EDX), 55% nanoparticles1Quantitative analysis in tissues, methodology reliable with some limitations Disdier et al. ( 2015 ) TiO 2 NPs, P25 (15–24 nm)1Quantitative analysis in blood and tissues, methodology reliable with some limitations Kreyling et al.…”
Section: Appendix G – Description Of Test Materials Scoring For Nanoscale Consideration and Internal Exposure For Toxicokinetic Studiesmentioning
confidence: 99%
“…However, placenta perfusion experiments with E171 suspension confirmed a low transfer of food-grade TiO 2 particles to the fetal side. The diameter of the TiO 2 particles recovered in the fetal exudate showed that 70 to 100% of particles were in the nanosized range [ 77 ]. These findings suggest that the human placenta barrier is not able to completely prevent the passage of TiO 2 nanoparticles to the fetus and emphasized the need to assess the risk of TiO 2 nanoparticles during pregnancy [ 77 ].…”
Section: Toxicokinetics Of Ingested E171mentioning
confidence: 99%
“…The possible reason might be different sizes for adopted TiO 2 NPs. The maternal-fetal transfer and accumulation of food-grade TiO 2 NPs in the human placenta and meconium emphasized the need for the risk assessment of chronic exposure to TiO 2 -NPs during pregnancy [75]. The protocol for black carbon detection in the placenta and evidence of them at the fetal side of human placenta.…”
Section: Introductionmentioning
confidence: 99%